THE ROLE OF THE MADRASAH HEAD IN MANAGING THE QUALITY OF EDUCATION IN THE PRIVATE MADRASAH ALIYAH AL-WASHLIYAH GADING, TANJUNGBALAI CITY - Arnida, Susi; Nahar, Syamsu; Hanum, Azizah (JURNAL TARBIYAH, 2023)
The aim of this research is to analyze programs, policies, implementation, monitoring and evaluation, influencing factors as well as obstacles and solutions and madrasa heads in managing the quality of educators in the Madrasah Aliyah Al-Washliyah Gading, Tanjungbalai City. The method used is qualitative with a phenomenological approach. The data sources were obtained from five people as informants, using interview techniques, observation and documentation studies. The results of research at the Al-Washliyah Gading Private Madrasah, Tanjungbalai City, show that the madrasa head's program for the quality of educators is RPP training, the yellow book learning method based on student activity, and teacher comparative studies. The implementation of the teacher quality development program has been carried out well through the implementation of management functions, as well as the supervision and evaluation of madrasah heads has gone well through class supervision and teacher work evaluation at the end of the semester. Supporting factors for madrasah heads to manage the quality of educators are time management, funds, facilities, teacher motivation and community demands. Meanwhile, the obstacles for madrasa heads in managing the quality of educators are limited funds and lack of discipline among educators. The madrasa head's solution for managing the quality of educators is cooperation and communicating well regarding the quality of educators, namely motivating educators and expanding relationships